Evaluation and Application of Radiochemical Neutron Activation to Noble Metal Analysis - Evans, Noreen J. (My University, 1987)
A rapid and simple radiochemical neutron activation technique involving tellurium coprecipitation of Au, lr, Pd and Pt was evaluated using the U.S.G.S. standards PCC-1 (peridotite) and DTS-1 (dunite) as well as a house standard, JHC-6 (spinifex zone of a komati itic peridotite). It was then applied to the analysis of samples of Archean greenstone from the Red Lake area.
The technique gives detection limits of 0.01-0.02, 0.02, 0.1-0.4 and 1-2 ppb for Au, Ir, Pd and Pt respectively and precisions of <25-35%. The method can be successfully applied to the analysis of PGE levels in sulphur-poor rocks, and large numbers of samples can be processed in a short period of time.
A comparison of PGE content between several types of mafic rocks was made as well as an investigation of possible secular trends (Archean vs. Phanerozoic) in PGE concentration.
Keywords: evaluation, application, radiochemical, neutron, activation, noble, metal, analysis, greenstone